The Belgian Repository of fundamental Atomic data and Stellar Spectra (BRASS). Issue Volume 15:Issue S350(2019) (April 2019) - Laverick, M.; Lobel, A.; Royer, P.; Merle, T.; Martayan, C.; van Hoof, P.; Van der Swaelmen, M.; David, M.; Hensberge, H.; Thienpont, E.
Abstract: The Belgian Repository of fundamental Atomic data and Stellar Spectra (BRASS) aims to provide one of the largest systematic and homogeneous quality assessment to date of literature atomic data required for stellar spectroscopy. By comparing state-of-the-art synthetic spectrum calculations with extremely high-quality observed benchmark spectra, we have critically evaluated fundamental atomic data, such as line wavelengths and oscillator strengths, for thousands of astrophysically-relevant transitions found in the literature and across several major atomic data repositories. These proceedings provide a short overview of the BRASS project to date, highlighting our recent efforts to investigate and quality-assess the atomic literature data pertaining to over a thousand atomic transitions present in FGK-type stellar spectra. BRASS provides all quality assessed data, theoretical spectra, and observed spectra in a new interactive database under development at brass.sdf.org .